Aplikasi Pembelajaran Biologi Berbasis Android Pada Siswa Kejar Paket C - Eka Prasetya Putra; Nonot Wisnu Karyanto; Nia Saurina (Melek IT : Information Technology Journal, 2017)
Education equality is education that takes place outside the school system, but the competence of its graduates are considered equivalent to the competence of graduates of formal education (schooling) after passing an equivalency test. One example of equality of education divided into 3 equal Elementary School Package A , Package B equivalent to junior high. and Package C equivalent to high school. In education equality C package there are many subjects one of which is Natural Sciences(IPA). Biology as one field IPA provides a variety of learning experiences to understand the concepts and processes of science. In biology, there are various kinds of materials one of which is the classification of living things. Classification of living things is a way of grouping (categorization). Currently, there are many students who did not understand the material classification of living things and have not been able to apply their knowledge in everyday life. This study uses a Rapid Application Development ( RAD) and interviews with Dikmas BPPAUD and East Java